Frontispiece: A Methoxydiphenylamine‐Substituted Carbazole Twin Derivative: An Efficient Hole‐Transporting Material for Perovskite Solar Cells. Issue 39 (18th September 2015) - Gratia, Paul; Magomedov, Artiom; Malinauskas, Tadas; Daskeviciene, Maryte; Abate, Antonio; Ahmad, Shahzada; Grätzel, Michael; Getautis, Vytautas; Nazeeruddin, Mohammad Khaja
Abstract : Solar Cells . M. K. Nazeeruddin et al. describe in their Communication on page 11409 ff. the synthesis of methoxydiphenylamine‐substituted carbazol, a hole‐transport material for perovskite solar cells.